Registry of Hypogonadism in Men (RHYME): design of a multi-national longitudinal, observational registry of exogenous testosterone use in hypogonadal men. (March 2013) - Rosen, Raymond C; Wu, Frederick C. W.; Behre, Hermann M.; Roehrborn, Claus G; Schröder, Fritz H.; Siami, Flora S.; Martha, Julia F.; Finn, Joseph D.; Araujo, Andre B.
Abstract Objective: Despite the prevalence of hypogonadism (HG) and widespread use of testosterone therapy, little is known about the safety/effectiveness of long-term testosterone use. The Registry of Hypogonadism in Men (RHYME) is a multi-national patient registry assessing prostate health and other outcomes associated with testosterone treatment in men. Design: Observational patient disease registry. Methods: RHYME is a non-interventional disease registry with longitudinal data collection on a large sample (N = 999) of well-characterized, hypogonadal men aged 18 years or older. The Registry will prospectively evaluate male patients diagnosed with HG, who have not previously been treated with testosterone therapy. Key design features include: (1) broad inclusion/exclusion criteria, (2) standardized central laboratory hormone assays, (3) independent adjudication of prostate biopsies and mortalities, (4) standard of care treatment, (5) comprehensive medical record and questionnaire data at six months and annually post-enrollment and (6) adequate statistical power for assessing prostate endpoints at 36 months. Results: A total of 25 clinical sites in six European countries (Germany, Italy, the Netherlands, Spain, Sweden and the United Kingdom) have completed recruitment for the study. Recruitment was initiated in May 2009, and completed in December 2011. Data collection is ongoing with a minimum of two years of follow-up on all patients.